2016
DOI: 10.1186/s12885-016-2897-6
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of serum CA 19-9 for patients with advanced lung adenocarcinoma

Abstract: BackgroundThis study aimed to assess the prognostic accuracy of serum CA 19-9 in patients with advanced lung adenocarcinoma.MethodsWe retrospectively reviewed data of 246 patients who were diagnosed at our institute with advanced (stage IIIB or IV) lung adenocarcinoma between March 2006 and December 2012. We excluded patients who received no chemotherapy, or for whom we had no data on pre-treatment tumor markers. We also evaluated 116 consecutive resected specimens from patients with clinical stage I lung aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…We excluded patients with comorbidities that could independently cause elevated serum CA19-9 levels from 1823 patients with NTM-PD. These comorbidities included stomach cancer 16 , colon cancer 17 , pancreatobiliary cancer 18 , 19 , lung cancer 20 , thyroid cancer 21 , benign hepatobiliary diseases 22 , 23 , thyroiditis 24 , and ovarian cysts 25 , 26 . The inclusion criteria were as follows: patients who underwent assessments for serum CA19-9 levels and chest CT scanning with an interval of less than 30 days between the two examinations and participants who underwent serum CA19-9 assessment in the time period between 1 month before the diagnosis and the initiation of NTM-PD treatment, which was considered as the active disease period of NTM-PD.…”
Section: Methodsmentioning
confidence: 99%
“…We excluded patients with comorbidities that could independently cause elevated serum CA19-9 levels from 1823 patients with NTM-PD. These comorbidities included stomach cancer 16 , colon cancer 17 , pancreatobiliary cancer 18 , 19 , lung cancer 20 , thyroid cancer 21 , benign hepatobiliary diseases 22 , 23 , thyroiditis 24 , and ovarian cysts 25 , 26 . The inclusion criteria were as follows: patients who underwent assessments for serum CA19-9 levels and chest CT scanning with an interval of less than 30 days between the two examinations and participants who underwent serum CA19-9 assessment in the time period between 1 month before the diagnosis and the initiation of NTM-PD treatment, which was considered as the active disease period of NTM-PD.…”
Section: Methodsmentioning
confidence: 99%
“…Malignant pulmonary diseases: Amongst lung cancer subtypes, CA 19-9 has potential in diagnosis, staging, prognostication, and prediction for complications and recurrences of Non-Small Cell Lung Cancer (NSCLC) specifically. However, a caveat is that only a minority of NSCLC patients express elevated CA 19-9 levels[ 107 , 108 ].…”
Section: Future Uses Of Ca 19-9mentioning
confidence: 99%
“…The prognostic role of CA 19-9 is controversial. A study by Sato et al [ 108 ] involving 246 Stage IIIB and Stage IV lung adenocarcinoma patients demonstrated that serum CA 19-9 was an independent prognostic marker in lung adenocarcinoma[ 108 ]. In contrast, another study by Tsoukalas et al [ 107 ] involving 100 NSCLC patients, who were not stratified by stage, showed that elevated CA 19-9 levels correlated with shorter OS, but could not prove CA 19-9 to be an independent prognostic factor[ 107 ].…”
Section: Future Uses Of Ca 19-9mentioning
confidence: 99%
See 1 more Smart Citation
“…Carbohydrate antigen 19-9 (CA 19-9) is isolated from a human colorectal cancer cell line. 7,9 Although applied in the diagnosis of pancreatico-biliary adenocarcinoma, it can be positive in advanced lung adenocarcinoma (ALADC) also. 10 CA 19-9 is extremely elevated in advanced lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%